Assessment of executive functions in school-aged children: A narrative review - Souissi, Sofiane; Chamari, Karim; Bellaj, Tarek (Frontiers in Psychology, 2022)
Introduction In the past three decades, there has been increasing interest in assessing children’s Executive Functions (EF). However, studies on the conceptualization and operationalization of this construct are incongruent and guidance for clinicians and researchers aiming to assess EF is insufficient due to measurement variability. Aims The purpose of this article was to examine current theories and models of EF in children, identify their assessment instruments, issues, and challenges, and discuss their impact on children’s cognitive, behavioral, social and/or emotional development. Methods This narrative review reflected on English and French scholarly articles on EF assessment in children. References were identified through searches of PubMed, Medline, ScienceDirect, Google Scholar, and APA PsychNet throughout the last two decades up to June 2022. Results There are commonalities despite divergence in the definition and operationalization of EF. Assessment of EF requires psychometric tests as well as rating scales that must be integrated and interpreted considering the child’s biological makeup, environmental background, and cultural specificities. Conclusion Current EF theories, assessment tools, issues, and challenges were discussed in addition to the impact of their components’ dysfunctions on children’s development. Further studies should be conducted to develop new measurement methods and technologies to improve the ecological and ethological validity of youth assessment, treatment, and interventions.